Avaliação do estado redox plasmático em pacientes com câncer através da determinação da capacidade oxidante e antioxidante total - Oliveira, Clarissa Aires de (2022)
Biology teaches that all vital functions are the final effect of an electric current generated by the sun, induced by the stimulation of specific photosensors (for example, chlorophyll) by visible and ultraviolet radiation. This evidence finally gives shape and substance to what philosophers and scientists over the centuries have understood or conceptualized as "vital flow." Considering that an electric current is a passage of electrons and that the transfer of electrons from a reducing species to an oxidant defines an oxidation-reduction reaction, we can say that it is the redox processes that, well controlled, sustain life, in all its forms. its manifestations, or make it more difficult, by illness, when out of control. In fact, redox processes, based on the transfer of reducing equivalents (isolated electrons or electrons linked to protons, in the form of hydrogen atoms) between certain chemical species, structurally predisposed to this, are involved in all vital phenomena, from metabolism control modulation of information flow. Therefore, redox processes are the main biochemical rings of conjunction between all living organisms, from prokaryotes to eukaryotes, from plants to animals, despite profound structural and evolutionary differences. The development of increasingly sophisticated techniques, some of which today allow us to see the development of some redox reactions "in vivo", has led in recent years to the definition of the concept of redox system and, therefore, to the development of modern redoxomics. The redox system is a ubiquitous biochemical system with adaptive purposes that, in response to a wide range of physical, chemical or biological stimuli, exploits the exchange of isolated reducing equivalents between oxidizing chemical species, biological targets and reducing chemical species to manage the signaling pathway. or defense essential for survival. In other words, the redox system is the biochemical system that specializes in controlling oxidative stress. Oxidative stress is a "biochemical declination" of the more general biological phenomenon of stress, understood as an immediate reaction to a threatening and potentially lethal event which, in the specific case of emotional stress, aims to predispose the subject to fight or flight. If the redox system response (eg, that associated with the cell membrane of neutrophilic granulocytes) is efficient, the threat (eg, a bacterial infection) is promptly neutralized, and the organism survives: oxidative eu-stress. If, on the other hand, the redox system is unable to manage the response (for example, due to genetic deficiencies, as seen in chronic granulomatosis), the organism may become ill or even succumb (for example, due to sepsis): distress oxidative. Just as maintaining a condition of oxidative eu-stress is desirable to promote or recover an optimal state of well-being and, therefore, achieve successful aging, also oxidative dys-stress can favor premature aging and/or pathological, also facilitating the appearance or worsening of metabolic, inflammatory and degenerative diseases, including cancer. Therefore, while oxidative eu-stress must be favored or at least not fought against, oxidative eu-stress must be prevented or eradicated if it is already underway. Therefore, a condition of oxidative stress can only be evidenced through specific laboratory tests, a prerogative of modern redoxomics. Some of these tests, such as the reactive oxygen metabolites (d-ROMs) test and the total antioxidant capacity (BAP) test, have established themselves over the last 20 years in several countries around the world due to their favorable cost/benefit ratio. , in terms of execution simplicity, analytical performance and, above all, the ability to show ex vivo alterations in the functioning of the redox system in specific clinical conditions, which the scientific literature refers to be associated with oxidative stress. We speak, in particular, of cancer. In this context, the aim of this dissertation is to present an original and up-to-date view of oxidative stress, unconventional, antinomic, between free radicals and antioxidants, as part of an equally original research work during which, for the first time, a population of patients Brazilians, in their specific clinical situation, were submitted to the evaluation of the plasmatic oxidative balance through the determination of the total oxidant capacity (d-ROMs test) and the biological antioxidant potential (BAP test). For didactic purposes, this work was divided into two chapters. Chapter 1 provides an overview of the etiopathogenesis of cancer in light of redox processes, in terms of changes in the redox system and oxidative stress. Chapter 2 refers to the experimental study that aimed to evaluate the redox status in a group of cancer patients residing in Brazil.